Application of Baseline Clinical and Morphological Parameters for Prediction of Late Stent Graft Related Endoleaks after Endovascular Repair of Abdominal Aortic Aneurysm. (July 2019) - Nolz, Richard; Schoder, Maria; Baltzer, Pascal; Prusa, Alexander; Javor, Domagoj; Loewe, Christian; Asenbaum, Ulrika
Abstract : Objectives: To evaluate the influence of baseline clinical and morphological parameters on the occurrence of a late stent graft related endoleak (srEL; types 1 and 3) after endovascular aneurysm repair (EVAR). Methods: This is a retrospective case control study of patients who were routinely followed up after EVAR of abdominal aortic aneurysms. Pre-interventional, pre-discharge, and last available multislice computed tomography angiogram (MSCTA) of 279 patients were analysed. Stent graft related endoleaks detected by follow up MSCTA at least six months after EVAR were specified as late srEL. Baseline demographic characteristics and morphological variables were derived from the pre-interventional and pre-discharge MSCTA. Univariable and multivariable analysis with a Cox proportional hazards model were used to determine baseline factors associated with the occurrence of a late srEL. Results: Twenty-four (8.6%) of 279 patients suffered a late srEL, during a mean MSCTA follow up of 30.9 ± 25.8 (23.5, IQR 10.6–42.8) months. In the univariable analysis, age (hazard ratio [HR] 1.09; p  = .001), female sex (HR 3.25; p  = .014), right iliac sealing diameter (HR 10.04; p  = .03), left iliac sealing diameter (HR 8.65; p  = .001), infrarenal aortic neck angulation (HR 1.02; p  = .011), and suprarenal fixation level (HR 3.47; p  = .014) were significantly associated with an increased incidence of late srEL. Age (HR 1.08; p  = .012), female sex (HR 2.72; p  = .049), and left iliac sealing diameter (HR 4.48; p  = .033) proved to be risk factors significantly associated with a higher incidence of late srEL in multivariable analysis. Conclusions: Older patients, those with female gender, and those with larger left iliac sealing diameters seem to experience higher rates of late srEL. Independent confirmation of these must be addressed in larger studies.